Jurisprudential and Legal Analysis of Crushing and Cracking of Spine Bone - reza poorsedghi; سیده ثریا موسوی (پژوهش‌های فقهی مسائل مستحدثه, 2023)
In penal law, the terms "crushing" and "cracking" of bones are distinct from fractures, carrying specific penalties. However, Article 647 of the Islamic Penal Code, which addresses rulings on spine damage, only mentions penalties for fractures, leaving ambiguity regarding whether it covers crushing or cracking. Surprisingly, this matter has not been addressed in Islamic jurisprudence either. The article aims to explore the issue by examining legal and jurisprudential evidence. Legal data reveals that the matter has not been addressed in legislation, falling within the realm of unlegislated cases. Consequently, determining the appropriate compensation (Diyyah) and retaliation (Arash) for spinal crushing and cracking requires reference to jurisprudence. Analysis of jurisprudential evidence further indicates that there are no established penalties for crushing and cracking of the spine in the hadīths and Sharīah sources. The evidence for a broken spine does not encompass crushing and cracking, while the evidence for bone crushing and cracking does not include the spine. Therefore, such damages fall under the purview of determining appropriate retaliation (Arash).